MORPHOLOGY OF ISCHEMIC INJURY OF LIVER ALLOGRAFT - L. V. Shkalova; I. M. Iljinsky; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
The literature data in modern transplantology concerning morphology of ischemic injury of liver allograft are analyzed in the article. Questions of pathogenesis of liver allograft ischemic injury, histological features that indicate the possibility of donor liver transplantation are discussed in detail, as well as the role of steatosis and its reverse is highlighted. We tried to systematize the morphological changes depending on severity of ischemic injury; also we focused on the questions of persistency of the ischemic injury in the liver allograft.